PERTUMBUHAN DAN PENINGKATAN PRODUKSI JAMUR TIRAM PUTIH (Pleurotus ostreatus) DENGAN FREKUENSI PEMBERIAN AIR LERI DAN AIR KELAPA PADA MEDIA BAGLOG - Hatta, M.; Abduh, A. D. (Percetakan Umi Toaha Makassar, 2026)
This study aimed to evaluate the effect of the frequency of application of Leri water and coconut water on mycelial growth, the time of primordia emergence, the number of fruiting bodies, the fresh weight of fruiting bodies, and the biological efficiency of white oyster mushrooms (Pleurotus ostreatus) grown on baglog media. A 2 x 3 factorial completely randomized design (CRD) with three replications was used in this study. The first factor was the type of nutrient solution (leri water and coconut water), and the second factor was the frequency of nutrient solution application (daily, every other day, and every three days). The results showed that the frequency of application of Leri water and coconut water significantly affected the growth and production parameters of white oyster mushrooms. Application of Leri water every other day showed the best results in terms of mycelial growth and biological efficiency, while daily application of coconut water had a positive effect on the number and fresh weight of fruiting bodies. The combination of nutrient solution type and application frequency significantly interacted with several growth and production parameters. This study provides valuable information for optimizing the use of leri water and coconut water as supplementary nutrients to increase white oyster mushroom productivity.